Dampak Risiko Likuiditas terhadap Profitabilitas pada Bank yang Terdaftar di Bank Indonesia - Andriansyah, Rizky; Fauzi, Restu Agung; Leon, Farah Margaretha (JURNAL AKUNTANSI DAN MANAJEMEN, 2024)
This study aims to identify variables that affect profitability in banking companies listed on the Indonesia Stock Exchange. The addition of credit risk variables as independent variables is a novel part of this study. This research method includes data collection from 20 banking companies over a five-year period (2019–2023) with a total of 100 data that meet the criteria with the application of data processing analysis using panel data regression analysis techniques. The results of the study found that liquidity risk has a significant negative effect on profitability, while the loan to deposit ratio and cash reserve ratio have a significant positive effect on profitability. Financial managers also need to be proactive in developing strategies, facing challenges, and adapting to technological developments in determining banking strategies to ensure the success of the bank. So investors need to consider the potential benefits and risks associated with credit risk because it can disrupt the performance of the banking sector, as well as conducting fundamental analysis and portfolio diversification to minimize risk. Investors also need to look at the operational side of the bank by paying attention to improving the bank's operational performance because this can increase the bank's income from various types of services, such as transaction fees, deposit interest, and loan fees.